ChemInform Abstract: Lewis Acid Promoted C—C and Copper‐Catalyzed C—O Bond Formation: Synthesis of Neoflavans. Issue 47 (6th November 2014) - Suchand, B.; Krishna, J.; Mritunjoy, K.; Satyanarayana, G.
Abstract A facile four‐step strategy for the synthesis of neoflavons is developed.